Knowledge Commercialization Framework: factors affecting developing countries (2021)
Amid economic pressure and inclination for independent financing, universities tend to commercialize knowledge, a growing trend emerging as an entry gate for the privatization of scientific advancements and the development and transfer of technology from universities. Numerous studies have been conducted on the commercialization of knowledge. This article aims to integrate previous studies and develop a comprehensive model out of the factors cited in those studies. Therefore, 57 relevant articles were analyzed to identify the indices of knowledge commercialization within the framework of a systematic review literature guideline. In addition to guideline validate criteria, three university professors were interviewed for conceptual model include the subjects (contextual, individual, organizational, institutional, and environmental), and components.